Conducting virtual assessments in developmental research: COVID-19 restrictions as a case example. Issue 1 (2nd January 2023) - Bogat, G. Anne; Wong, Kristyn; Muzik, Maria; Lonstein, Joseph S.; Nuttall, Amy K.; Levendosky, Alytia A.; Colao, Cara F.; Hall, Alanah; Cochran, Kara; Forche, Kathryn R.; Koneczny, Allison; Gareffa, Amanda; et al.
Abstract: Developmental researchers face considerable challenges regarding maximizing data collection and reducing participant attrition. In this article, we use our experiences implementing our study on the effects of timing of prenatal stress on maternal and infant outcomes during the COVID-19 pandemic as a framework to discuss the difficulties and solutions for these challenges, including the development of two types of virtual assessments. Specific information regarding use of virtual platforms, confidentiality, engaging children during video conferencing, and modifying the major assessments of our research are discussed. Feasibility data are presented, and data analytic challenges regarding statistical inference are outlined. Finally, we conclude with some of the unintended positive consequences for our research that resulted from making these modifications to our original methods.